2020
DOI: 10.1155/2020/8857580
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Viscoelastic Solution of the Frost Heaving Force of Cavity Water behind Tunnel Linings

Abstract: With the high demand for construction of tunnels in China’s severe cold regions, the problem of frost heaving has become an important factor that endangers tunnel safety. This paper attempts to investigate the effect of frost heave of cavity water that widely exists in the tunneling engineering on the tunnel stability. According to the actual deformation of the surrounding rock of the tunnel, the viscoelastic behavior is considered to the surrounding rock. On the premise of the elastic solution of stagnant wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…e Bingham model is composed of elastic element and ideal viscoplastic body in series, which cannot reflect the nonlinear creep behavior characteristics of geotechnical materials [23]. In order to describe the nonlinear creep behavior of soil under cyclic loading, a modified Bingham constitutive model (see Figure 4) is proposed by replacing the constant elastic and viscous elements in the Bingham model with nonlinear elements.…”
Section: Elastic-viscoplastic Model Based On the Bingham Modelmentioning
confidence: 99%
“…e Bingham model is composed of elastic element and ideal viscoplastic body in series, which cannot reflect the nonlinear creep behavior characteristics of geotechnical materials [23]. In order to describe the nonlinear creep behavior of soil under cyclic loading, a modified Bingham constitutive model (see Figure 4) is proposed by replacing the constant elastic and viscous elements in the Bingham model with nonlinear elements.…”
Section: Elastic-viscoplastic Model Based On the Bingham Modelmentioning
confidence: 99%
“…Zone. e generalized Kelvin model is widely used in rock mass engineering because it can describe the elastic hysteresis of rock mass and reflect instantaneous deformation characteristics [33][34][35][36][37][38]. Considering the time effect of stress redistribution in the plastic zone during its formation, this paper analyzed the creep characteristics of rock by using the generalized Kelvin model [39,40].…”
Section: Creep Analysis In Elasticmentioning
confidence: 99%
“…e stress of composite lining support structure is calculated by equations ( 30)- (32) and checked by equations ( 33), (36), and (38). Finally, the stress characteristics under specific engineering geological conditions are determined, which provides a reference for the design of support structure and stability evaluation.…”
Section: Calculation Of Lining Ultimate Bearing Capacitymentioning
confidence: 99%
“…Considering the combined effect of the rock elastic modulus and the void ratio, Liu et al (2019) proposed a damage model for frost heaving pressure of tunnel linings. More relevant studies could be found in the works of Lv et al (2019), Yan et al (2019), Zhang et al (2019), Guo et al (2020), Huang et al (2020) and Zhao et al (2020).…”
Section: Introductionmentioning
confidence: 99%